Biochemical Changes and Germination Response of Indian Sandalwood (Santalum album L.) Seeds Subjected to Biopriming Techniques and Variable Post-priming Storage - , Harish Debta, T.K. Kunhamu, A.V Santhoshkumar, V. Jamaludheen, N.K. Binu, K.C. Jisha (Archives of Current Research International, 2024)
Understanding of the storage behaviour of endangered plant species such as Indian Sandalwood, Santalum album L. is important for successful conservation. We tested biopriming method with five biopriming agents (e.g. Effective microorganisms; Plant growth promoting rhizobacteria (PGPR-I and PGPR-II); Pseudomonas fluorescens and Piriformospora indica) with four uniform durations of treatments viz. 2, 4, 6 and 8 days. Hydropriming was also performed with similar condition for comparison of seed performance. The study examined the biochemical changes that occur in Sandalwood seeds during different post-priming storage periods (0, 30, 60, 90 days) to assess the efficacy of biopriming techniques on seed germination and health. Biopriming with Pseudomonas fluorescens for eight days recorded the highest germination percentage (70.67%) and the highest germination rate index (0.84). Longer durations of PGPR-I and Piriformospora indica treatment (6-8 days) lowered the imbibition period and mean germination time while increasing the germination rate. After a post-priming storage period of 30 days, only EM and Pseudomonas fluorescens treated seeds germinated while all other treatments failed to germinate. Absence of germination in any biopriming group at 60 and 90 days storage period indicated that the sandal seeds deteriorated over extended storage period. The reduction in seed viability of sandal seeds was consequent to the changes in the biochemical characteristics and action of enzymes (α and β amylases) involved in seed food reserve depletion and loss in membrane integrity.